(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The aim of this study was to assess the outcomes of endoscopic surgery for suturing perforated duodenal bulb ulcers at E Hospital from January 2018 to December 2022. Research Method: A retrospective study was conducted on 122 patients with perforated duodenal bulb ulcers who underwent endoscopic suturing at the Department of Gastrointestinal Surgery and General Surgery, E Hospital , from January 2018 to December 2022 Results: All cases involved a single anterior duodenal bulb perforation. The success rate of endoscopic suturing for duodenal bulb perforated ulcers was 121 out of 122 cases, with one case requiring conversion to open surgery. The average surgical duration was 77.55 ± 28.5 minutes, and no intraoperative complications were recorded. Postoperative pain was low, as evidenced by the use of pain medication for an average of 2.7 ± 1.8 days. The average time for resumption of bowel movements was 3.42 ± 1.71 days. There were no cases of gastric output exceeding 500ml per day, and abdominal drainage was removed after 6.1 ± 2.5 days. 89.4% of patients had follow-up appointments scheduled for one year after surgery, and 12.3% experienced mild epigastric discomfort. Late complications included hypertrophic scars (2 cases), stenosis at the anastomotic site (1 case), recurrent perforation (1 case), and recurrent ulceration at the suture site (5 cases). Conclusion: Endoscopic surgery for suturing perforated duodenal bulb ulcers offers several benefits for patients. It is associated with a shorter treatment duration, reduced postoperative pain, low complication rates, and low mortality rates.